ANALISIS PERMINTAAN AIR BERSIH PDAM KELOMPOK RUMAH SEDERHANA KOTA BANDA ACEH - Sarah Marisi Manurung; Ferayanti Ferayanti (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2021)
This research aims to analyze the demands of clean water from PDAM Kota Banda Aceh customers in the lower middle class house. The variables in this research are the demand of clean water (Y), family incomes (X1), family members (X2), number/s of motor vehicles (X3), ownership of water sources outside PDAM (X4), and PDAM tariffs (X5). The primary data of this research is obtained from questionaries which given to 100 respondents of PDAM’s lower middle class house customers. The data is analyzed using Spearman Rank Test in order to understand the correlation between variables and the strength of bond from correlation coefficient value. From this research the researcher found that there is no significant correlation coefficient value between family incomes, family members, number/s of motor vehicles, and ownership of water sources outside PDAM with the demand of clean water. On the other hand, there is a significant correlation between PDAM tariffs and the demand of clean water. Thus, PDAM tariffs shows strong correlation bonding with the demand of clean water from PDAM customers in Kota Banda Aceh. The researcher hopes PDAM Kota Banda Aceh can keep increasing their service qualities, so they can reach the target of Peraturan Presiden (PERPRES) Nomor 2 Tahun 2015 about RPJMN (Rencana Pembangunan Jangka Menengah Nasional) which 100% of clean water service to every society in 2035.Keywords: Clean Water Demand, Lower Middle Class House, Family Income, Family Members, PDAM tariffs.